Oceny moralne w procesie wyrokowania przez sąd karny - Mazur, Paweł (ETHICS IN PROGRESS, 2013)
The article Moral judgments within processing by criminal court. An overview is designed to be an introduction to problems of moral evaluations within criminal process. It is stated that evaluations necessarily contribute to sentences´ guilty or unguilty and judges pass them to achieve justice. Let us call chosen institutions of penal law to show how problematic axiologica reasoning and evaluative procedures can really be. There is no universal or higher moral system in which judge's evaluations would be rooted. Each judge needs to develop his own moral judgment competence. Courts have to justify values-based sentences to make them convincing for the whole society.